2013
DOI: 10.1016/j.apergo.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Predicting discomfort from whole-body vertical vibration when sitting with an inclined backrest

Abstract: Current methods for evaluating seat vibration to predict vibration discomfort assume the same frequency weightings and axis multiplying factors can be used at the seat surface and the backrest irrespective of the backrest inclination. This experimental study investigated the discomfort arising from whole-body vertical vibration when sitting on a rigid seat with no backrest and with a backrest inclined at 0 (upright), 30, 60, and 90 (recumbent). Within each of these five postures, 12 subjects judged the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 31 publications
2
26
1
Order By: Relevance
“…In a later study, at the higher magnitudes and at frequencies greater than 1.0 Hz, there was some discomfort in the head as well as in the central parts of the body (Basri and Griffin 2013). As frequencies increased, the head became a less important location for discomfort in favour of the upper back and the lower back.…”
Section: Body Locations Showing Greatest Discomfortmentioning
confidence: 76%
See 1 more Smart Citation
“…In a later study, at the higher magnitudes and at frequencies greater than 1.0 Hz, there was some discomfort in the head as well as in the central parts of the body (Basri and Griffin 2013). As frequencies increased, the head became a less important location for discomfort in favour of the upper back and the lower back.…”
Section: Body Locations Showing Greatest Discomfortmentioning
confidence: 76%
“…Jang and Griffin 2000), the inclination of backrests (e.g. Basri and Griffin 2013), effects of low frequency rotation (e.g. Beard and Griffin 2013), and the effects of mechanical shocks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the subjects sat in comfortable upright postures without touching a backrest and they wore a loose lap belt. Sitting posture and contact with a backrest can alter the frequency-dependence of discomfort caused by vertical vibration (Basri and Griffin, 2013) and it might be expected that with greater magnitude shocks the tightness of a belt may alter discomfort. These factors need to be taken into account when applying the findings of the study FIGURE 9 ABOUT HERE…”
Section: Comparing Equivalent Comfort Contours For Vibration and Shocmentioning
confidence: 99%
“…However, seats usually have inclined backrests and it has been reported that the W c weighting overestimates the discomfort caused by x-axis vibration of inclined backrests at low frequencies and underestimates at frequencies greater than 8 Hz (Kato and Hanai, 1998;Basri and Griffin, 2011). Furthermore, with increasing inclination of a backrest there is greater support for the upper-body and the relative importance of vertical seat pan vibration is reduced (Basri and Griffin, 2012;2013). It is not known how well a SEAT value based on currently standardised weightings will predict the overall vibration discomfort when sitting in a compliant seat with an inclined backrest.…”
Section: Introductionmentioning
confidence: 99%